Synthesis of novel carbazole hydrazine-carbothioamide scaffold as potent antioxidant, anticancer and antimicrobial agents - Capan, Irfan; Hawash, Mohammed; Qaoud, Mohammed T.; Gulum, Levent; Tunoglu, Ezgi Nurdan Yenilmez; Cifci, Kezban Ucar; Tutar, Yusuf (Bmc, 2024)
Background Carbazole-based molecules containing thiosemicarbazide functional groups are recognized for their diverse biological activities, particularly in enhancing therapeutic anticancer effects through inhibiting crucial pathways. These derivatives also exhibit noteworthy antioxidant properties.Objectives This study aims to synthesize, characterize, and evaluate the antioxidant and anticancer activities of 18 novel carbazole derivatives.Methods The radical scavenging capabilities of the compounds were assessed using the 2,2-diphenyl-1-picrylhydrazyl assay. Antiproliferative activities were evaluated on MCF-7 cancer cell lines through viability assays. Additionally, the modulation of the PI3K/Akt/mTOR pathway, apoptosis/necrosis induction, and cell cycle analysis were conducted for the most promising anticancer agents.Results nine compounds showed potent antioxidant activities with IC50 values lower than the positive control acarbose, with compounds 4 h and 4y exhibiting the highest potency (IC50 values of 0.73 and 0.38 mu M, respectively). Furthermore, compounds 4o and 4r displayed significant anticancer effects, with IC50 values of 2.02 and 4.99 mu M, respectively. Compound 4o, in particular, exhibited promising activity by targeting the PI3K/Akt/mTOR signaling pathway, inhibiting tumor survival, inducing apoptosis, and causing cell cycle arrest in MCF-7 cell lines. Furthermore, compound 4o was showed significant antimicrobial activities against S. aureus and E. coli, and antifungal effect against C. albicans. Its potential to overcome drug resistance through this pathway inhibition highlights its promise as an anticancer agent. Molecular docking simulations supported these findings, revealing favorable binding profiles and interactions within the active sites of the enzymes PI3K, AKT1, and mTOR. Moreover, assessing the druggability of the newly synthesized thiosemicarbazide derivatives demonstrated optimal physicochemical properties, further endorsing their potential as drug candidates.
Keywords: Carbazole; Thiosemicarbazide; Antioxidant; Anticancer; PI3K/Akt/mTOR pathway; Molecular docking